Prevention of diabetic foot ulcers: Analysis of the performance of Primary Health Care Professionals (Research, Society and Development, 2023)
Diabetes is a chronic metabolic disease whose number of people with the disease has increased considerably in recent years. Among the complications, diabetic foot ulcers stand out. To prevent this complication, daily care for the health and feet of people with diabetes is necessary, so that the disease does not take hold and cause physical and emotional damage, such as the formation of ulcerations and even amputation. The work of health professionals, especially doctors and nurses who work in primary health care, is fundamental in educating patients about correct habits and attitudes, and periodically evaluating and examining their feet. Objective: to analyze the actions carried out by primary care health professionals, doctors and nurses, to prevent diabetic foot ulcers. Methodology: To this end, doctors and nurses who work in the Family Health Team of a municipality in Minas Gerais were interviewed. Results: it was observed that professionals do not know the equipment needed to examine feet, in addition to not adopting care protocols aimed at this public. Conclusion: Although they report carrying out the necessary guidelines to prevent diabetic foot ulcers, it is important to rethink the care procedures aimed at people with diabetes, and in preventing complications.